A Comparative Assessment of Carbon Stock Potential and Regeneration Status Between Natural and Plantation Forests in Southwest Ethiopia - Shetie Gatew; Mekonnen Zerihun (International Journal of Forestry Research)
Forests play a key role in combating climate change by sequestering and storing carbon from the atmosphere through photosynthesis. This study compares the carbon stock potential and regeneration status between natural and plantation forests in the Derashe special district, Southwest Ethiopia. The study involved collecting of data from 90 20 × 20 m plots for trees, 5 × 5 m plots for seedlings and saplings, and 1 × 1 m plots for soil, litter, herb and grass, aboveground biomass and carbon stock were measured using allometric equations, while belowground biomass was calculated based on the ratio of belowground to aboveground biomass. Soil organic carbon (SOC) was determined from organic carbon content in three soil layers (0–10 cm, 10–20 cm, and 20–30 cm). The regeneration potential was assessed by counting seedlings, saplings, and mature trees. Data analysis was performed using two independent t-tests and one-way ANOVA. The results showed that the average total biomass carbon density of natural forests (271.57 tons·ha−1) was higher than that of plantation forests (259.23 tons·ha−1). There was no significant difference in aboveground biomass carbon, belowground biomass carbon, and deadwood biomass carbon between the two forest types. However, significant differences (p<0.05) were found in SOC, litter, herb and grass biomass carbon, and stump deadwood biomass carbon. The total number of seedlings, saplings, and mature trees were 127, 107, and 813 in natural forests, and 169, 62, and 1030 in plantation forests, respectively. Both forest types exhibited poor regeneration, as the number of seedlings and saplings was lower compared to mature trees, indicating forest degradation. The Gardula forest stores a total of 530.8 tons ha-1 carbon. In general, both plantation and natural forests in Gardula have significant carbon storage potential and contributing to national and global efforts to mitigate climate change.